Surface roughness optimization based on hybrid harmony search and artificial bee colony algorithm in electric discharge machining process - Deris A.M.; Solemon B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric discharges; Optimal systems; Optimization; Surface roughness; Artificial bee colonies (ABC); Artificial bee colony algorithms; Convergence rates; Electric discharge machining (EDM); Hybrid approach; Numerical applications; Optimal solutions; Surface roughness (Ra); Electric discharge machining